1980
DOI: 10.1161/01.hyp.2.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sodium and potassium intake with excretion.

Abstract: SUMMARY Nine weU-motirated adults, knowledgeable about nutrition, kept food records, sared food portions equal to what had been eaten, and collected 24-hour urine samples for 3 consecutive days. Estimates of sodium and potassium intake were calculated from food table analyses of written food records and from flame photometric analyses of food portions. For each subject the mean of the estimates for each of the 3 days was compared with the mean of urine analyses for sodium and potassium for each of the 3 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 5 publications
5
56
1
2
Order By: Relevance
“…However, it has been demonstrated that dietary recall information on sodium consumption parallels 24-h urinary sodium excretion. 31 Potassium intake ranged from 1508.2 to 1673.1 mg/day, which is far less than the estimated minimum requirements of 2000 mg. 30 Dietary factors that contributed significantly to the blood pressures of hypertensive children are remarkably similar to those indicated as deficiencies in primary school children of South Africa. 32 Vorster et al 32 observed iron, vitamin A, folic acid and calcium deficiencies in preschoolers and primary school children.…”
Section: Discussionmentioning
confidence: 83%
“…However, it has been demonstrated that dietary recall information on sodium consumption parallels 24-h urinary sodium excretion. 31 Potassium intake ranged from 1508.2 to 1673.1 mg/day, which is far less than the estimated minimum requirements of 2000 mg. 30 Dietary factors that contributed significantly to the blood pressures of hypertensive children are remarkably similar to those indicated as deficiencies in primary school children of South Africa. 32 Vorster et al 32 observed iron, vitamin A, folic acid and calcium deficiencies in preschoolers and primary school children.…”
Section: Discussionmentioning
confidence: 83%
“…Creatinine. Assuming that the rate of urinary creatinine excretion is constant (Pollack, 1970), 24-hour excretion of creatinine has been used as a standard to exclude urine collections judged to be incomplete (Doyle, Chua & Duffy, 1979;Schachter et al, 1980;Ljungman et al, 1981). However, there is a wide range in individual excretion of creatinine related to body mass and diet.…”
Section: Measures Of Completeness Of 24-hour Urine Collectionsmentioning
confidence: 99%
“…Shortt et al (1988) have calculated that a sample size of at least 30 subjects would be required to estimate group mean sodium intake with a standard error of less than 5% assuming the availability of a single 24 h sample. Subsequently, several 24 h urine collections are necessary to characterize an individual's usual sodium intake (Liu et al, 1979;Schachter et al, 1980). Information obtained from 24 h urines will, provided they are complete, be more accurate than figures estimated from spot samples, samples from the first urination in the morning or timed overnight collections.…”
Section: Sodiummentioning
confidence: 99%